(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The article presents the results of multi-factor experimental studies conducted on the justification of the optimal values of the parameters of the combined machine for applying organic fertilizers to pomegranate orchards, then, in order for the combined machine to ensure the required quality of work at 3-5 km/h working speeds, the surface of the fertilizer drop slot of the metering device should be 849.4-938.0 cm2, the number of revolutions of the star of the metering device should be in the range of 60.2-63.1 r/min. At these values of the factors, the mass of the fallen fertilizer was 3.64-4.75 kg, and the distance of the fertilizer falling was 40.5-57.6 cm.